Cutural mediation in between controversies (Palíndromo, 2019)
Since the Queermuseum case, the expectation that the task of educational programs is to correct the ‘audiences’ misunderstandings’ with respect to modern or contemporary art has been significantly questioned. The point is that different audiences, based on values almost always unrelated to the presuppositions and debates of the art world, have been contrary to the realization of certain exhibitions and works of art, with an unprecedented vehemence and repercussion. What, then, is the role of mediation in the face of such rejections? In this article, we use the methodology proposed by Nathalie Heinich (2010) for a sociology of values, that is, “a good use of neutrality”, to propose a reformulation of the attributions and ways of doing cultural mediation in the context of education in art exhibitions and museum spaces; one that takes into account its investigative, documentary, post-critical and properly political aspects.
Keywords: cutural mediation; culture wars; Queermuseum case